2015
DOI: 10.1080/15438627.2014.975809
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine Supplementation after Anterior Cruciate Ligament Reconstruction in Athletes: A Randomized Placebo-controlled Trial

Abstract: Although glucosamine is commonly consumed by athletes, its effectiveness in sports injuries is still under debate. We aimed to investigate the effects of glucosamine to the rehabilitation outcomes of anterior cruciate ligament (ACL) reconstructed athletes. Glucosamine-sulfate (1000 mg daily, for 8 weeks) was administered to half of the cohort of 30 male athletes, the other half used a placebo. Both groups received the same rehabilitation protocol. Knee pain and functions were evaluated by a visual analogue sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 48 publications
0
8
0
6
Order By: Relevance
“…Indeed, although proper knowledge on nutrition and DSU, including the information based on high-quality peer reviewed research, should be crucial for safe and effective DSU, this problem is evidently understudied in professional athletes. Specifically, it is generally accepted that athletes consume DSs to improve their recovery and performance and/or to overcome the lack of certain nutrients for specific reasons (i.e., vegetarianism, female athletes during their menstrual cycle) [2124]. However, due to the competitive spirit of sports, athletes are particularly vulnerable to aggressive DS marketing.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, although proper knowledge on nutrition and DSU, including the information based on high-quality peer reviewed research, should be crucial for safe and effective DSU, this problem is evidently understudied in professional athletes. Specifically, it is generally accepted that athletes consume DSs to improve their recovery and performance and/or to overcome the lack of certain nutrients for specific reasons (i.e., vegetarianism, female athletes during their menstrual cycle) [2124]. However, due to the competitive spirit of sports, athletes are particularly vulnerable to aggressive DS marketing.…”
Section: Introductionmentioning
confidence: 99%
“…The studies have shown that it may be viable to conclude that it is not necessary to include creatine or glucosamine supplementation in the rehabilitation regimen for patients recovering from ACLR surgery. 22,23 Cryotherapy. Unrelieved postoperative pain may impair rehabilitation, compromise functional outcomes, and lead to patient dissatisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…[30] This drug is not only specific to cartilage cells, but also affects the cells such as the ones in the ligament and tenocytes. [20] Although it was shown that GlcN-CS did not have a positive effect on rehabilitation of the athletes with anterior cruciate ligament repair, Özer et al [30] and Eraslan and Ulkar [31] showed that GlcN-CS complex increased the synthesis of collagen and also that collagen type is more organized.…”
Section: Discussionmentioning
confidence: 99%